Global vegetation dynamics : concepts and applications in the MC1 model - Bachelet, Dominique; Turner, David (Washington, D.C. : American Geophysical Union ; Hoboken, NJ : Wiley, 2015)
MC1 is a widely used dynamic global vegetation model (DGVM) that has been used to simulate potential vegetation shifts in National Parks (NPs) such as Wind Cave NP and Yosemite NP, across various states such as California and Alaska, over the entire continent of North America, and even over the entire globe, under a variety of climate change scenarios. Global Vegetation Dynamics: Concepts and Applications in the MC1 model describes the creation in the mid-1990s, architecture, uses, and limitations of the MC1 DGVM that is being used by an increasing number of research groups around the world.
8.3. RESULTS8.4. DISCUSSION; ACKNOWLEDGMENTS; REFERENCES; Chapter 9 Simulating Effects of Climate and Vegetation Change on Distributions of Martens and Fishers in the Sierra Nevada, California, Using Maxent and MC1; ABSTRACT; 9.1. INTRODUCTION; 9.2. METHODS; 9.3. RESULTS; 9.4. DISCUSSION; ACKNOWLEDGMENTS; REFERENCES; Part III Packaging MC1 Results to Increase Its Usability by Managers; Chapter 10 Using a Dynamic Global Vegetation Model to Help Inform Management Decisions; ABSTRACT; 10.1. INTRODUCTION; 10.2. DEVELOPING CLIMATE-INFORMED STSMs; 10.3. cSTSM MODEL APPLICATION IN CENTRAL OREGON.
Includes bibliographical references and index.
Text in English.
Vendor-supplied metadata.
Keywords: Vegetation dynamics -- Computer simulation; Vegetation and climate -- Computer simulation; Plant succession -- Simulation methods; Vegetation dynamics -- Simulation methods; Vegetation dynamics; SCIENCE -- Life Sciences -- Botany; Electronic books; Electronic books